Analytic Survey of Benin City residents’ viewership of Select Faith Based TV Stations in Nigeria - Achilike, Njoku Ignatus (Pancasila International Journal of Applied Social Science, 2025)
This study, entitled "Analytic survey of Benin City residents’ viewership of select Faith Based TV stations in Nigeria," explored the viewership impact of Dove TV and Loveworld TV on the spiritual lives of residents in Benin City, Nigeria. The primary objectives include examining the extent of viewership, identifying factors influencing the preference for these stations, and assessing their perceived impact on viewers' spirituality. The researcher employed the Uses and Gratification Theory to understand audience motivations, while a survey research design is utilized, with a structured questionnaire as the primary instrument for data collection. The findings revealed that a significant portion of the population engaged with these faith-based channels, primarily due to quality content, perceived credibility, and accessibility. The study indicated that viewers experience increased spiritual knowledge and strengthened faith, although gaps in community engagement and local relevance have been identified. In conclusion, the study emphasized the importance of Dove and Loveworld TV in fulfilling spiritual needs while suggesting that these stations should invest in community outreach initiatives, enhance program development with local voices, and explore the evolving role of faith-based media in different cultural contexts for future research.